Analisis Pola Konsumsi Rumah Tangga Petani Kelapa Sawit di Kabupaten Labuhanbatu - Zulkarnain Nasution; Khairul Rizal; Junita Lubis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The household is the smallest unit in society, so it can be said that household income means community income. This study aims to determine the determination of the variable income, economic activity, and household members, as well as differences in the location of residence to the consumption of oil palm farmers in Labuhanbatu Regency. The method used to analyze data with multiple linear regression models, by certifying in the Least Square Dummy Variable (LSDV) method. The estimation results found that all independent variables were positive and significantly influenced the amount of food consumption, on the contrary were negative and significant towards non-food consumption expenditure. The estimation results also found that the amount of consumption of various types of foodstuffs in urban communities was smaller than the food consumption of inland communities amounting to Rp.1,248,000. However, greater than the consumption of food for coastal communities is Rp. 1,323,800. While the amount of consumption expenditure for various types of non-food for urban communities is greater than non-food consumption for inland communities Rp.2,782,000. And also greater than non-food consumption of coastal communities, namely Rp. 3776 000. Variation in the ability of independent variables in explaining food consumption by 92.5 percent, and expenditure for non-food consumption by 87.4 percent. The model specification is very good with the model being free from violations of the classical assumptions of multicollinearity and heterokedastisitas. Keywords: Consumption, Income, Socio-economy, Oil palm Farmers